ANALYSIS OF THE EFFECT OF EXPORTS, IMPORTS, AND INFLATION RATE ON FOREIGN EXCHANGE RESERVES IN INDONESIA - Abidah Dwi Rahmi Satiti; Rivatul Ridho Elvierayani; Sukmawati Indah Dzikria (Sean Institute, 2023)
The position of Indonesia's foreign exchange reserves during the last 5 years had been fluctuated, causing disruption to the Indonesian economy. This study was conducted to determine the effect of exports, imports, and inflation on Indonesia's foreign exchange reserves. This study uses a causal relationship research design with a quantitative approach. The sample of this research is monthly data from Indonesia's foreign exchange reserves, exports, imports, and inflation for the 2016-2020 period. The data used is secondary data in the form of time series obtained from the BI and BPS websites. The analysis tool uses multiple linear regression analysis, with SPSS version 20. The results show that partially exports have a significant positive effect, imports have no effect on Indonesia's foreign exchange reserves, inflation has a significant negative effect on Indonesia's foreign exchange reserves. Simultaneously, exports, imports, and inflation have a significant effect on Indonesia's foreign exchange reserves.